2003
DOI: 10.1093/emboj/cdg442
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Mnt leads to disrupted cell cycle control and tumorigenesis

Abstract: Mnt is a Max‐interacting transcriptional repressor that has been hypothesized to function as a Myc antagonist. To investigate Mnt function we deleted the Mnt gene in mice. Since mice lacking Mnt were born severely runted and typically died within several days of birth, mouse embryo fibroblasts (MEFs) derived from these mice and conditional Mnt knockout mice were used in this study. In the absence of Mnt, MEFs prematurely entered the S phase of the cell cycle and proliferated more rapidly than Mnt+/+ MEFs. Defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
163
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(184 citation statements)
references
References 39 publications
18
163
3
Order By: Relevance
“…However, it was recently shown that the expression of Mnt was reduced in six out of 14 medulloblastoma tumors analysed and Mnt was therefore suggested to be a potential tumor suppressor (Cvekl et al, 2004). This notion is supported by the findings that Mnt loss mimics Myc overexpression and confers apparent tumorigenic advantage in Mnt-null MEFs and in cells with downregulated Mnt expression (Hurlin et al, 2003;. It will be interesting to see whether disruption of the Mnt-mSin3 interaction and thus loss of Mnt-mediated repression is a common mechanism in cancer development.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, it was recently shown that the expression of Mnt was reduced in six out of 14 medulloblastoma tumors analysed and Mnt was therefore suggested to be a potential tumor suppressor (Cvekl et al, 2004). This notion is supported by the findings that Mnt loss mimics Myc overexpression and confers apparent tumorigenic advantage in Mnt-null MEFs and in cells with downregulated Mnt expression (Hurlin et al, 2003;. It will be interesting to see whether disruption of the Mnt-mSin3 interaction and thus loss of Mnt-mediated repression is a common mechanism in cancer development.…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, downregulation of Mnt by siRNA resulted in induction of cdk4 and cyclin E in quiescent cells. These two proteins have previously been shown to be upregulated in Mnt null mouse embryo fibroblasts (MEFs), and thus represent potential Mnt target genes (Hurlin et al, 2003). In contrast, the cyclin D2 levels were shown to be unaffected in Mnt-null primary fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further complexity is provided from the fact that Myc : Max dimers can play the other side of the field, repressing transcription by binding to and disrupting the functions of other transcriptional activators such as Miz-1 (Figure 1c Herold et al, 2002;Kime and Wright, 2003;Wu et al, 2003). And, as a final blow to convention, there are now reasonable alternatives as to how the network really works, as Myc can effectively displace Mnt : Max complexes, and Mnt loss alone, even in somatic cells that express no forms of Myc, is capable of inducing the 'Myc' response (Hurlin et al, 2003;Nilsson et al, 2003) (Figure 1b).…”
Section: The Max Network Bluesmentioning
confidence: 99%
“…Indeed there is scant evidence from knockouts in mice, or knockdowns of more archaic forms in Drosophila, that loss of c-Myc, N-Myc, Max, or any of the Mads triggers apoptosis in vivo, although effects on cell mass, rates of cell cycle traverse and/or proper differentiation are evident (reviewed in Baudino and Cleveland, 2001). The same cannot be said for Mnt, as loss of Mnt in mouse embryo fibroblasts (MEFs) (Hurlin et al, 2003) or knock down of Mnt using RNA interference is sufficient to trigger apoptotic programs. Strikingly, since Mnt loss can provoke apoptosis even in somatic cells lacking all forms of Myc (Mateyak et al, 1997), this indicates that Myc may trigger apoptotic programs indirectly, by effectively disrupting Mnt's functions in harnessing the apoptotic response .…”
Section: The Max Network Bluesmentioning
confidence: 99%